Uso de válvulas redutoras de pressão na otimização de rede setorizada de distribuição de água - Sousa, Renato de (2017)
This research aimed to perform an energy and hydraulic analysis of a sectorized water supply system. An intelligent control system based on fuzzy logic was used, which has the function of controlling the pressure reducing valves. This control system aims to control the downstream pressures of the valves to reduce the high pressure of the pipes, in order to reduce volume lost by leaks, induced consumption or even ducts rupture. In this way, the controller will cause the system to adapt to the maximum consumption level, in order to balance the pressures in all consumption points, aiming to avoid the inefficient supply to consumers located in distant points or of higher topographies. The reduction valve opens or closes according to the pressure levels of each sector, transferring pressure energy from higher pressure levels to lower pressure levels. All the work was done in an instrumented and automated experimental bench intending to simulate a consumption dynamics in which two sectors consume different volumes of water.